Case study: The characterization and implementation of dielectric spectroscopy (biocapacitance) for process control in a commercial GMP CHO manufacturing process. (14th February 2019) - Moore, Brandon; Sanford, Ryan; Zhang, An
Abstract: Dielectric spectroscopy (biocapacitance) is an up‐and‐coming technology for real time monitoring of biomass in cell culture processes and has opened the door for next‐generation cell culture process control techniques such as automated on‐demand nutrient feeding. In this case study we empirically demonstrate the lower limit of quantitation (LOQ), probe‐to‐probe consistency, and scalability of in situ biocapacitance probes using data generated from small‐ and large‐scale Chinese hamster ovary (CHO) bioreactor cultures. The process understanding experiments culminated in the use of biocapacitance for process control in the current good manufacturing practices (GMP) manufacturing environment, first to automate the dilution of seed train cultures during scale‐up stages and later as a method of predicting future glucose demand. The automated biomass‐probe‐based inoculation strategy yielded consistent results in six consecutive seed trains in the GMP manufacturing suite. In the process of improving our understanding of the technology we determined that biocapacitance could additionally be used as an indicator of a shift in the salt balance of a cell culture, and that collecting real time biomass data via biocapacitance has the potential to reduce the total timeline for feed strategy development by providing additional insights into culture performance which are not otherwise apparent using conventional optical cell counting methods.